Revitalisasi Seni Membatik Khas Jambi sebagai Instrumen Pemberdayaan Perempuan: Integrasi Etnopedagogi, Ekonomi Kreatif Syariah, dan Ketahanan Budaya Lokal - Denny Defrianti; Fhadilla, Azzahra; Febrianti, Anisha; Nurul Hadrah, Andi; Niken Dwi Oktafia, Abelya (Pendidikan Sejarah FKIP Universitas JAMBI, 2026)
The existence of Nusantara's local traditions faces significant challenges due to the massive flow of information in the 21st-century digitalization era, which risks eroding local wisdom along with its philosophical, historical, and sociological values. In response to this shift, higher education institutions are demanded to transform into cultural preservation agents as well as driving forces for community empowerment. This community service article presents and analyzes a women's empowerment model involving members of the Dharma Wanita Persatuan (DWP) of the Faculty of Science and Technology, State Islamic University (UIN) Sulthan Thaha Saifuddin Jambi, through vocational training in making batik with distinctive local motifs at Rumah Batik Siti Hajir, Seberang Kota Jambi. Utilizing a qualitative approach and the Asset-Based Community Development (ABCD) framework, this study integrates the epistemological values of Jambi Batik with the 5P social engineering approach (Enabling, Empowering, Protecting, Supporting, and Maintaining). The results describe that the application of andragogy principles, the utilization of ethnomathematics values, and Halal Ecoprint innovation are capable of generating a comprehensive empowerment impact. The batik training has transformed from a mere motor activity into a sharia creative economy incubator that fosters household financial independence. Simultaneously, this initiative strengthens the community's sociocultural resilience against the impacts of urban alienation, positions women as agents of cultural inheritance, and forms an integrated ecosystem in alignment with the implementation of the Tridharma (Three Pillars) of higher education.